Offering fragile X syndrome carrier screening: a prospective mixed-methods observational study comparing carrier screening of pregnant and non-pregnant women in the general population. Issue 9 (9th September 2013) - Martyn, M; Anderson, V; Archibald, A; Carter, R; Cohen, J; Delatycki, M; Donath, S; Emery, J; Halliday, J; Hill, M; Sheffield, L; Slater, H; et al.
Abstract : Introduction: Fragile X syndrome (FXS) is the leading cause of inherited intellectual and developmental disability. Policy development relating to carrier screening programmes for FXS requires input from large studies examining not only test uptake but also psychosocial aspects. This study will compare carrier screening in pregnant and non-pregnant populations, examining informed decision-making, psychosocial issues and health economics. Methods and Analysis: Pregnant and non-pregnant women are being recruited from general practices and obstetric services. Women receive study information either in person or through clinic mail outs. Women are provided pretest counselling by a genetic counsellor and make a decision about testing in their own time. Data are being collected from two questionnaires: one completed at the time of making the decision about testing and the second 1 month later. Additional data are gathered through qualitative interviews conducted at several time points with a subset of participating women, including all women with a positive test result, and with staff from recruiting clinics. A minimum sample size of 500 women/group has been calculated to give us 88% power to detect a 10% difference in test uptake and 87% power to detect a 10% difference in informed choice between the pregnant and non-pregnant groups. Questionnaire data will be analysed using descriptive statistics and multivariate logistic regression models. Interview data will be thematically analysed. Willingness-to-pay and cost effectiveness analyses will also be performed. Recruitment started in July 2009 and data collection will be completed by December 2013. Ethics and Dissemination: Ethics approval has been granted by the Universities of Melbourne and Western Australia and by recruiting clinics, where required. Results will be reported in peer-reviewed publications, conference presentations and through a website http://www.fragilexscreening.net.au . The results of this study will make a significant contribution to discussions about the wider introduction of population carrier screening for FXS.